Development of processing equipment for souvenir production from wood and plastics wastes (2018)
Wood wastes and consumer waste plastic wastes are abundant and constitute menace in the environment. the present means of disposing these wastes are ineffective and the machines for processing wood plastic composite are expensive, high energy consumption, required high technical know-how and are not readily available. this work was therefore designed to develop a processing equipment from locally available material s, that are cheap, energy efficient, and effective for the production of souvenirs from wood and consumer waste plastic bottles. the machines consist of melting and mixing chamber, temperature control unit, heating unit, the stirrer, the moulding unit, discharge chute and the support frame unit. a batch production takes 2hrs 45minutes with a throughput of 7.2kg/hr and machine efficiency of 72.5%. the properties of wood plastic composite produced were sorption properties (water absorption and thickness swelling), density, flexural and tensile. these were found suitable for non-structural applications and were used for souvenir productions such as broom base, picture frame, flower pots and office accessories.